Cause-of-injury analysis in European antidumping actions - Brian Hindley (European Centre for International Political Economy (ECIPE), 2009)
To impose antidumping duties consistently with the WTO, a national antidumping authority must show that the dumping has caused injury to the domestic industry producing a like product. Antidumping methodology splits this requirement into two component questions: a. does the local industry producing a like product display symptoms of injury?; and b. are these symptoms caused by dumping? The European Commission is good at finding positive answers to question (a) but less good at answering (b). An Annex to this paper provides a detailed examination of ten recent cases. It finds that the Commission's conclusions with respect to question (b) are questionable in at least five of the ten.
Keywords: 330; WTO-Recht; Dumping; Antidumping; EU-Recht; EU-Staaten; Welt